A organizaçao do trabalho pedagógico da Educaçao Física e a carreira docente - Oliveira, Ivan Bremm de; Frizzo, Giovanni Felipe Ernst (2019)
The objective of this research was to analyze the organization of the pedagogical work of Physical Education (PE) teachers in different moments of the teaching career. This is a case study with 04 EF teachers from the Municipal Network of Teaching of Pelotas, RS, with one, 14, 21 and 31 years of teaching based on participant observation and semi-structured interviews. We find out that the objectives of EF at the beginning of their careers are broad and become more specific and related to schooling afterwards; already in the evaluation, it starts from a more informal level and goes to a prevalence of formal aspects. As regards the contents, the sportivization of the classes crossed the teaching career. With respect to the methods, they start with the prioritization of experiences of sports practices and difficulties of concretization of a pedagogical theory trying to articulate a method to the game. Thus, throughout the career there is a greater elaboration of the constituent elements of the organization of the pedagogical work.
O objetivo desta pesquisa foi analisar a organizaçao do trabalho pedagógico do professorado de Educaçao Física (EF) em diferentes momentos da carreira docente. Trata-se de um estudo de caso com quatro professores de EF da Rede Municipal de Ensino de Pelotas- RS, com um, 14, 21 e 31 anos de docência, a partir da observaçao participante e entrevistas semiestruturadas. Constatamos que os objetivos da EF no início da carreira apresentam-se de forma ampla e vao tornando-se mais específicos e relacionados com a educaçao escolarizada; já na avaliaçao, parte-se de um nível mais informal para a prevalência de aspectos formais. Nos conteúdos, a esportivizaçao das aulas perpassou a carreira docente. Nos métodos, parte-se da priorizaçao de vivências de práticas esportivas e dificuldades de concretizaçao de uma teoria pedagógica, tentando-se articular um método ao jogo. Assim, ao longo da carreira há uma maior elaboraçao dos elementos constituintes da organizaçao do trabalho pedagógico.
Keywords: Pedagogical work; Teaching career; Teaching experience; Physical Education; Trabalho pedagógico^lpt; Carreira docente; Experiência docente; Educaçao física